Digital technology and job quality: multidimensional insights from the labor market in East Java - Putri, Jatu Mawar Widhiarti; Pratomo, Devanto Shasta; Susilo, Susilo (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2026)
Digital technology transformation has a significant impact on labor market dynamics, both in terms of job quantity and quality. This study aims to analyze the extent to which digital technology influences workers’ job quality in East Java Province using a multidimensional approach. The measurement method used in this study is the Job Quality Index (JQI) developed by the World Bank, which assesses four dimensions of job quality: income, security, benefits, and job satisfaction. This study uses 2023 Sakernas data, comprising 39,425 observations. The analytical method employed is binary logistic regression. Robustness tests across various model specifications are conducted to ensure the stability of the results. The findings show that using digital technology increases the likelihood of achieving better job quality by up to 2.3 times compared to non-users. Other individual characteristics, such as education, training, gender, and age, also positively influence workers’ job quality. Conversely, participation in the Pre-Employment Card (Prakerja) Program and living in urban areas are found to have negative effects. This study highlights the importance of digital literacy and inclusion, as well as human capital investment through education and competency-based training aligned with labor market needs.